2014
DOI: 10.1038/ncomms4967
|View full text |Cite
|
Sign up to set email alerts
|

pT305-CaMKII stabilizes a learning-induced increase in AMPA receptors for ongoing memory consolidation after classical conditioning

Abstract: The role of CaMKII in learning-induced activation and trafficking of AMPA receptors (AMPARs) is well established. However, the link between the phosphorylation state of CaMKII and the agonist-triggered proteasomal degradation of AMPARs during memory consolidation remains unknown. Here we describe a novel CaMKII-dependent mechanism by which a learning-induced increase in AMPAR levels is stabilized for consolidation of associative long-term memory. Six hours after classical conditioning the levels of both autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 58 publications
(87 reference statements)
1
17
0
Order By: Relevance
“…Several studies have demonstrated that CaMKII is a critical regulator of memory consolidation (e.g., Chen, Bambah-Mukku, Pollonini, and Alberini, 2012; Halt et al, 2012; Naskar, Wan, and Kemenes, 2014; Ota, Monsey, Wu, and Schafe, 2010; Wan, Mackay, Iqbal, Naskar, and Kemenes, 2010), but despite this evidence, little is known about how CaMKII regulates memory reconsolidation following retrieval (Arguello et al, 2014; Da Silva et al, 2013; Sakurai et al, 2007). One theory is that CaMKII is involved in transcriptional and subsequent translational regulation in neurons following retrieval (Tronson and Taylor, 2007), as well as AMPA receptor trafficking (Johansen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that CaMKII is a critical regulator of memory consolidation (e.g., Chen, Bambah-Mukku, Pollonini, and Alberini, 2012; Halt et al, 2012; Naskar, Wan, and Kemenes, 2014; Ota, Monsey, Wu, and Schafe, 2010; Wan, Mackay, Iqbal, Naskar, and Kemenes, 2010), but despite this evidence, little is known about how CaMKII regulates memory reconsolidation following retrieval (Arguello et al, 2014; Da Silva et al, 2013; Sakurai et al, 2007). One theory is that CaMKII is involved in transcriptional and subsequent translational regulation in neurons following retrieval (Tronson and Taylor, 2007), as well as AMPA receptor trafficking (Johansen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, because they possess relatively simple nervous systems with identifiable neurons, it has been possible to study at the single neuron level the changes underlying learning and memory. Another important advantage possessed by these systems is that because they have an open circulatory system the concentrations of peptides and sugars in the hemolymph are thought to be similar to those in the CNS (Lee et al, 2012;Lukowiak, Sunada, Teskey, Lukowiak, & Dalesman, 2014;Matsuo, Kawaguchi, Yamagishi, Amano, & Ito, 2010;Naskar, Wan, & Kemenes, 2014;Noboa & Gillette, 2013;Otsuka et al, 2013;Walker, Campodonico, Cavallo, & Farley, 2010;Takigami et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Lymnaea stagnalis snails have been used extensively for the analysis of cellular and molecular mechanisms of locomotion (Syed and Winlow, 1991b;Pavlova, 2010;Longley and Peterman, 2013), feeding (Benjamin and Rose, 1979;Elliott and Benjamin, 1989;Kemenes and Elliott, 1994;Staras et al, 1998Staras et al, , 2003Alania et al, 2004;Vehovszky et al, 2005;Vavoulis et al, 2007;Chistopolsky and Dyakonova, 2012), respiration (Syed and Winlow, 1991a,b;Tsyganov et al, 2004;Bell et al, 2007), learning and memory (Kemenes et al, 1997(Kemenes et al, , 2002Kojima et al, 1997;Spencer et al, 1999;Staras et al, 1998;Jones et al, 2003;Sangha et al, 2003;Kemenes et al, 2006;Nikitin et al, 2008;Marra et al, 2013;Mita et al, 2014;Naskar et al, 2014), and decision making (Pirger et al, 2014;Crossley et al, 2016). There are also approaches that have been developed only in this organism, particularly the studies at the single-cell level of freshly isolated, not cultured, neurons (Dyakonova et al, 2009(Dyakonova et al, , 2015Dyakonova and Dyakonova, 2010), and experimental tests of an extracellular chemical microenvironment that has been demonstrated to play a prominent 'socializing' role in adjusting single-cell physiology to the network state (Dyakonova et al, 2015).…”
Section: Risky Decision Making By Snails In a Vital Situationmentioning
confidence: 99%